ANALISIS PENENTUAN LOKASI RETAIL MENGGUNAKAN SISTEM INFORMASI GEOGRAFI DI KECAMATAN TEMBALANG DAN BANYUMANIK KOTA SEMARANG - Pangi, Pangi; Dwi Astuti, Khristiana; Prasetyaning Sukmawati, Dian; Warasambi Mispaki, Syachril (Jurnal Perencanaan dan Pengembangan Kebijakan, 2025)
Tembalang and Banyumanik Districts in Semarang City are experiencing rapid growth due to their educational and settlement functions, as well as the presence of the main Trans Java Toll Road. This growth necessitates increased investment and the development of modern retail spaces. However, unplanned retail expansion could lead to spatial conflicts. To address this, this study aims to determine the optimal locations for modern retail development using Geographic Information Systems (GIS). By considering spatial planning patterns, consumer preferences, and factors like population density, accessibility, and proximity to activity centers, the study will overlay these factors to identify potential retail locations. The ArcGIS software will be used for overlay-based spatial analysis to determine the most suitable locations. The results of this study explain the allocation of retail locations divided into four alternative locations. These alternative location categories are: first, second, third, and fourth. These recommendations will serve as a foundation for modern retail planning in Semarang City, supporting the preparation of detailed spatial plans (RTRW or RDTR) for the urban area.